Reversible Mg-Metal Batteries Enabled by a Ga-Rich Protective Layer through One-Step Interface Engineering - Shin, Sunghee; Kwak, Jin Hwan; Oh, Si Hyoung; Kim, Hyung-Seok; Yu, Seung-Ho; Hee-Dae Lim (American Chemical Society, 2023)
Practical applications of Mg-metal batteries (MMBs) have been plagued by a critical bottleneck─the formation of a native oxide layer on the Mg-metal interface─which inevitably limits the use of conventional nontoxic electrolytes. The major aim of this work was to propose a simple and effective way to reversibly operate MMBs in combination with Mg(TFSI)2-diglyme electrolyte by forming a Ga-rich protective layer on the Mg metal (GPL@Mg). Mg metal was carefully reacted with a GaCl3 solution to trigger a galvanic replacement reaction between Ga3+ and Mg, resulting in the layering of a stable and ion-conducting Ga-rich protective film while preventing the formation of a native insulating layer. Various characterization tools were applied to analyze GPL@Mg, and it was demonstrated to contain inorganic-rich compounds (MgCO3, Mg(OH)2, MgCl2, Ga2O3, GaCl3, and MgO) roughly in a double-layered structure. The artificial GPL on Mg was effective in greatly reducing the high polarization for Mg plating and stripping in diglyme-based electrolyte, and the stable cycling was maintained for over 200 h. The one-step process suggested in this work offers insights into exploring a cost-effective approach to cover the Mg-metal surface with an ion-conducting artificial layer, which will help to practically advance MMBs.